Applied approach to entomology during the last forty-years in Panama - Atencio-Valdespino, Randy (2022)
Introduction. Insects are associated with human communities, with positive and negative impacts within each society. This aspect is the basis of the study of insects as a science called entomology, which involves the development of various branches. Due to the social and economic importance of this science in various areas of Panamanian society, a significant development has been achieved during the last forty years. Objective. To determine the branches of entomology applied in Panama during the last four decades. Development. The development of entomology in Panama focused on promoting general, agricultural, veterinary, medical, and forensic entomology through the development of research, teaching, and the establishment of the necessary foundations to promote science. Conclusions. Five branches, including general, agricultural, veterinary, medical, and forensic entomology, constituted the cornerstone and the impetus for the development of entomology as a science for forty years at the service of Panamanian society, justified by social needs related to health, food, and the economic aspects. In recent years topics such as the environment, climate change, and sustainability have also been included.